Spots and Clots – Leave Them or Treat Them? Why and How to Treat - Dennis M Jensen (Canadian Journal of Gastroenterology)
The clinical indication for urgent endoscopy with combined diagnosis and treatment is bleeding that is severe enough to seek medical attention. The author uses stigmata of ulcer hemorrhage as a guide to endoscopic therapy. Active arterial bleeding, nonbleeding visible vessels and adherent nonbleeding clots are always treated endoscopically. In randomized trials, patients have demonstrated better outcomes from endoscopic therapies than from medical therapies. Flat spots, grey or black sloughs, and clear ulcer bases are not treated endoscopically. The clinical condition and the endoscopic appearance of the ulcer (ie, stigmata of hemmorrhage) of the patient with upper gastrointestinal bleeding are used to determine the subsequent level of care (discharge, ward or intensive care).